2011
DOI: 10.1111/j.1540-5907.2011.00541.x
|View full text |Cite
|
Sign up to set email alerts
|

Polarizing Cues

Abstract: People categorize themselves and others, creating ingroup and outgroup distinctions. In American politics, parties constitute the in- and outgroups, and party leaders hold sway in articulating party positions. A party leader's endorsement of a policy can be persuasive, inducing co-partisans to take the same position. In contrast, a party leader's endorsement may polarize opinion, inducing out-party identifiers to take a contrary position. Using survey experiments from the 2008 presidential election, I examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
241
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(259 citation statements)
references
References 49 publications
14
241
0
4
Order By: Relevance
“…I explore whether the strength of partisanship can disconfirm the racial-political stereotypes that are normally applied to minority candidates. Because the strength of party labels plays such a strong role in affirming voter attitudes (Rahn, 1993;Nicholson, 2011), I hypothesize that a Democratic partisan affiliation will feed into pre-existing racial-political stereotypes and that this will lead to a racial bias against minority Democratic candidates. This bias should manifest itself in respondents rating their minority Democrats as more ideologically extreme.…”
Section: When Does Race Matter?mentioning
confidence: 99%
“…I explore whether the strength of partisanship can disconfirm the racial-political stereotypes that are normally applied to minority candidates. Because the strength of party labels plays such a strong role in affirming voter attitudes (Rahn, 1993;Nicholson, 2011), I hypothesize that a Democratic partisan affiliation will feed into pre-existing racial-political stereotypes and that this will lead to a racial bias against minority Democratic candidates. This bias should manifest itself in respondents rating their minority Democrats as more ideologically extreme.…”
Section: When Does Race Matter?mentioning
confidence: 99%
“…This process might lead to a polarization spiral, in which voters' adherence to party lines gets even stronger, since the split between them and an out-group gets clearer (Druckman et al, 2013), and the radicalization of supporters drives party elites toward them in turn. It has been observed that a politician's endorsement of a policy might have a polarizing effect not only by lining up her own supporters behind it, but by generating repulsion for it from opponents (Nicholson, 2012).…”
Section: How Can Prrp's Contribute To Mass Polarization?mentioning
confidence: 99%
“…Even so, most evidence to date suggests that, on political issues, individuals generally lack such motivation and instead fall back on 5 This coheres with social identity theory-indeed, motivated reasoning should be driven by individuals' desire to be loyal to and consistent with their own group and to maximize difference with the outgroup. Partisan groups are clearly important to political categorization (Nicholson 2012;Smith et al 2005). 6 It is implied that we expect perceptions of frame effectiveness to mediate the process by which the frame will influence overall attitude.…”
mentioning
confidence: 99%